Significados da obesidade na perspectiva dos usuários da atenção primária à saúde de Palmas-TO - Silva , Andreza Domingos da (Universidade Federal do Tocantins, 2022)
This research contemplates one of the specific objectives of the project to Combat and Control Obesity in the Scope of the SUS of Tocantins (ECOA SUS/TO) which aims to understand the meanings of obesity from the perspective of users with Basic Health Units in Palmas-TO. It is a descriptive, exploratory study, with an interpretivist epistemological position as a means of qualitative approach studies, through content analysis. The collection was carried out in October 2020, through an individual interview, supported by a semi structured script, in a virtual environment (online), in a synchronous way, by videoconference using the Google Meet tool. Eight people with obesity were also analyzed from the results, with certain categories, with the following: People with obesity and with the health process also expanded, considering their factors and the concept of obesity, but considering their factors and the concept of obesity , reductionist of the absence of diseases; They have knowledge about health promotion, but experience its applicability in the territory; Identify the positive changes in their lifestyles with support from the nutritionist, especially regarding the practice of physical activity and healthy eating; Understanding as overweight, relating to height, the processes of illness and obesity; They identify as strategies to face obesity, the need for adequate care by the multiprofessional team, but assume responsibility for their health condition; and presents an existence of several feelings linked to its obesity. Therefore, it can be deepened that this project is extremely relevant in terms of approaching the understanding of body obesity with several meanings, physical and psychological, mainly related to image dissatisfaction, due to being overweight, that of a difficult disease. reversal, anger in a limiting and stigmatizing way that converge in the production of feelings of sadness, sadness, discrimination (fatphobia), indifference, stress, aggressiveness and great concern for their health condition. It is expected that these results can generate human changes in the care of people with obesity in the SUS in a more empathic and humanized way.